GEOLOGI DAN PROSPEK GEOWISATA PERBUKITAN JIWO, BAYAT, JAWA TENGAH - -, Sutanto (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2008)
Jiwo Hills, Bayat is one of the three place in Jawa that pre-tertiary and paleogene rocks are exposed, the other two are at Karangsambung, Central Java and Ciletuh, West Ja-va. These rocks consist of metamorphics, igneous and sedimentary rocks where some of them able to proposed as geotourism sites.The spesific rocks outcrope and olso its spe-cific relation exposed at Bendungan, Sekarbolo, Watuprahu, Bukit Temas and Bukit Jo-kotuwo. The oldest rocks at the Jiwo Hills is pre-Tertiary Phillyte Lithodem, its consist phyllites, mica schist, chlorite schist and marble that unconformably covered by Eocene Gamping-Wungkal Formation. Phyllite Litodem and Gamping-Wungkal Formation are cutted by some Late Eocene to Early Oligocene (39.8, 33.2 dan 31,3 Ma) basaltic oroge-nic dyke. These thee litologic units (formation) are unconformably covered by Oyo For-mation that concist of calcarenite and marl stratification. The Geotourism sites in the Jiwo Hills are the ideal places for the object study and researh for students and geologists. At last, we propose to preserve all the object geotourism at the Jiwo Hills as natural labora-tory for earth sciences.